IMPACT OF CHEMICAL HERBICIDES TO BREAD WHEAT GENOTYPES (Triticum aestivum L) - Al-Latif, M.R.A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate effect of wheat cultivates to herbicides. A field experiment was conducted at the Research Station of the Field Crops Department at the College of Agricultural , University of Tikrit during winter season 2017-2018. Factorial Experiment within Randomized Complete Block design with three replicates were used . This experiment contains two variables first was used the herbicide (Atlantis, Pallas, Chevalier) and control. The second variable includes four cultivates (Al-Hashimiyah, Al-Baraka, Nor, and Door 29). The results Al-Baraka revealed that the highest plant height (75.91 cm), number of spikes (372.67 m2) and the number of shoots m2 (355.41), while the cultivate Noor had the highest value, number of grains spike-1 (42.67) and the total grain yield (4.82) ton ha-1. Atlantis herbicide recorded the highest number of tillers square meter-1 (387.50) and the treatment Balas recorded the highest value in the weight of a thousand grains (40.24 g) and total grain yield (2.00 tons . ha-1). The interaction between genotypes and pesticides produced highest grain yield (6.31) tons.ha-1.